FINITE ELEMENT NUMERICAL ANALYSIS FOR FATIGUE STRENGTH IN FSW WELDING OF ALUMINUM-5052 ALLOY - Armansyah, Armansyah; Setyanto, Djoko (Indonesian Journal of Engineering and Science, 2025)
This study applied observations on the fatigue loads of friction stir welding joints of 5052 Aluminum alloy using the finite element method approach. The 3-dimensional model of the test specimen for fatigue loading was designed using CAD software following the ASTM E466 standard. Fatigue loads were simulated numerically using Ansys Workbench software with loading sequences of 5000 N, 10,000 N, 15,000 N, and 20,000 N. The simulation showed a significant increase in equivalent stress from about 9.44e7 Pa to 3.82e8 Pa.. Deformation increased from 0.32 mm to 1.26 mm, while equivalent static strain rose from 0.001 m/m to 0.004 m/m. The S/N curve analysis showed that fatigue life was under 500,000 cycles at loads between 10,000 and 20,000 N, and between 500,000 and 6,000,000 cycles at 5000 to 10,000 N.